أثر التنمية الذاتية للفرد المسلم في ضوء التربية الإسلامية (The Impact of Self-Development of Individual Muslim in the Light of Islamic Education) - Ali Qasim, Mohamad Sarhan; Abdul Kadir, Fakhrul Adabi; Berahim@Ibrahim, Ahmad Zaki; Mohamad, Ali (Journal of Al-Tamaddun, 2011)
This research highlights the various aspects of self-development and its impact on the Muslim individual in light of Islamic Education. It first introduces the concept and characteristics of self-development in Islam, and explains how Islam is concerned with special type of development through naming some of its aspects and inferences made from the Qur'an and the Sunnah. Such a development however, relates to the effective viewing of experience, and to the statements of the means assigned to Muslims to achieve self-development. This paper also discusses the impacts affecting the individual through self-development. This research uses curriculum indicatives based on the Qur'an and Sunnah that are related to self-development. The results include self-development which embraces development of individual skills and abilities in various fields. It targets a higher goal of changing for the better, and the need to achieve self-development for society in general, particularly those in a position of authority and responsibility. This research also shows that complementary aspects of self-development in Islam are many; they include faith and worship, science, morality, productivity and physical well-being.